ANALYSIS OF THE PROVISION OF EMERGENCY SURGICAL CARE IN THE REPUBLIC OF NORTH OSSETIA-ALANIA FOR 2021-2023 - Zaurbek V. Totikov; Valeriy Z. Totikov; Zara R. Alikova; Irina T. Totikova; Ramina A. Khubetsova; Ruslan A. Hallaev; Timur T. Kaziev (Siberian Journal of Life Sciences and Agriculture)
Background. Emergency abdominal surgical pathology accounts for a significant proportion of hospital deaths. The most common emergency abdominal conditions include acute appendicitis, intestinal obstruction, perforated gastric and duodenal ulcers, gastrointestinal bleeding, strangulated hernias, acute cholecystitis, and acute pancreatitis. Regular analysis of emergency department data is essential to identify any problems that exist and develop strategies for addressing them.